Network tailoring of organosilica membranes via aluminum doping to improve the humid-gas separation performance. Issue 10 (16th February 2022) - Moriyama, Norihiro; Ike, Misato; Nagasawa, Hiroki; Kanezashi, Masakoto; Tsuru, Toshinori
Abstract : Al doping densified and hydrophilized the pore structure of organosilica membranes, which resulted in improved permselectivity in humid-gas separation at moderate-to-high temperature. Abstract : Organosilica membranes have recently attracted much attention due to excellent hydrothermal stability which enables their use in the presence of water. In particular, during humid-gas separations at moderate-to-high temperatures, these membranes have shown excellent water permeance and moderate water selectivity, which has been a breakthrough in separation performance. In the present work, we found that aluminum doping into the bis(triethoxysilyl)ethane (BTESE)-derived organosilica structure further improves water selectivity (H2 O/N2, H2 O/H2 ) while maintaining a level of water permeance that reaches as high as several 10 −6 mol (m −2 s −1 Pa −1 ). Single-gas permeation and nitrogen adsorption experiments have revealed that aluminum doping promotes densification of the pore structure and improves molecular sieving. In addition, water adsorption and desorption experiments have revealed that aluminum doping enhances water adsorption onto the pore walls, which blocks permeation by other gasses and significantly improves water permeation selectivity during the separation of humid gases. Our results provide a strategy for the fabrication of a membrane that provides both a high level of water permeance and enhanced water selectivity.